NAZARUDDIN'S CASE: THE JAKARTA POST REPORTS ON A BRIBERY ATTEMPT CASE - RIDHA, Fachru (2013)
The aims of this study entitled "Nazaruddin Case: The Jakarta Post Reports on a Bribery Attempt Case" are to describe The Jakarta Post schemata in reporting the case, to investigate how the major participants are reported in the texts, and to uncover meanings constructed from the text. The study focuses on news reporting Nazaruddin's bribery attempt case which has been published by English news sites in Indonesia: The Jakarta Post (www.thejakartapost.com). Five related articles have been selected. The analyses of these reports comply with the frameworks of Critical Discourse Analysis, especially Van Dijk framework, Sociogognitive Approach (SCA) (2009). First, macropropositions and news schemata are examined, described, and interpreted on the level of macrostructure and superstructure.These levels are used to see the ways of Nazaruddin case are reported in the text. Then, these are followed by an examination of participants based on the representations using microstructure analysis. Finally, these three levels of analysis will lead this study to uncover meaning constructed from the text. The study finds that, based on macrostructure and superstructure analysis, The Jakarta Post reports the news carefully and the readers are left to draw their own conclusions. Meanwhile, based on microstructure analysis, the major participants in the text are Nazaruddin and Mahfud. Nazaruddin is represented negatively, while Mahfud is represented positively. It means The Jakarta Post dislikes what Nazaruddin has done. In addition, negative representation of Nazaruddin influences the representation of institution in which he worked in. Key Words: The Jakarta Post, discourse, macrostructure, superstructure, microstructure, and meaning.